2011
DOI: 10.1111/j.1542-2011.2011.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Depression and Correlated Factors in Women Who Received In Vitro Fertilization Treatment

Abstract: A higher frequency of IVF treatment, cesarean birth, and inadequate social support increase the possibility of postpartum depression, and clinicians should provide appropriate anticipatory education or counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 34 publications
3
9
1
Order By: Relevance
“…In developed countries, unplanned pregnancy (Chee et al, 2005;Eilat-Tsanani et al, 2006;Ege et al, 2008;Kozinszky et al, 2011;Goker et al, 2012;Gaillard et al, 2014) and mode of delivery (Green et al, 2006;Eisenach et al, 2008;Kim et al, 2008;Davey et al, 2011;Lee et al, 2011;Goker et al, 2012;Koutra et al, 2014;Raisanen et al, 2013;Gaillard et al, 2014) showed mixed findings. Koutra et al (2014) showed a statistically significantly high level of mean postpartum depression score among mothers who underwent cesarean section, consistent with Lee et al (2011). Cohort studies shows that mode of delivery is not associated with postpartum depression (Kim et al, 2008;Gaillard et al, 2014) and that the severity of acute pain response to childbirth predicts postpartum depression (Eisenach et al, 2008).…”
Section: Obstetric and Pediatric Factorsmentioning
confidence: 92%
See 1 more Smart Citation
“…In developed countries, unplanned pregnancy (Chee et al, 2005;Eilat-Tsanani et al, 2006;Ege et al, 2008;Kozinszky et al, 2011;Goker et al, 2012;Gaillard et al, 2014) and mode of delivery (Green et al, 2006;Eisenach et al, 2008;Kim et al, 2008;Davey et al, 2011;Lee et al, 2011;Goker et al, 2012;Koutra et al, 2014;Raisanen et al, 2013;Gaillard et al, 2014) showed mixed findings. Koutra et al (2014) showed a statistically significantly high level of mean postpartum depression score among mothers who underwent cesarean section, consistent with Lee et al (2011). Cohort studies shows that mode of delivery is not associated with postpartum depression (Kim et al, 2008;Gaillard et al, 2014) and that the severity of acute pain response to childbirth predicts postpartum depression (Eisenach et al, 2008).…”
Section: Obstetric and Pediatric Factorsmentioning
confidence: 92%
“…Studies in both developed (Boyce and Hickey, 2005;Chee et al, 2005;Green et al, 2006;Hunker et al, 2009;Escriba-Aguir and Artazcoz, 2011;Kozinszky et al, 2011;Lanes et al, 2011;Lee et al, 2011;Quelopana et al, 2011;Sword et al, 2011;Eastwood et al, 2012) and developing (Aydin et al, 2005;Chee et al, 2005;Inandi et al, 2005;Husain et al, 2006;Wang and Chen, 2006;Dindar and Erdogan, 2007;Liabsuetrakul et al, 2007;Ege et al, 2008;Gausia et al, 2009;Yagmur and Ulukoca, 2010) countries show that the lack of social support is an independent predictor of postpartum depression. Other less studied factors significantly related to postpartum depression in developed countries are migration status (EilatTsanani et al, 2006;Gaillard et al, 2014) and domestic violence (McGrath et al, 2008;Dennis and Vigod, 2013).…”
Section: Socio-demographic Factorsmentioning
confidence: 97%
“…Researchers and clinicians need to further examine how women respond to these measures prior to undergoing IVF in order to determine whether these measures warrant routine clinical use. The purpose of this study was to 1) examine response profiles in women preparing for IVF, and 2) compare their responses to those of postpartum women – a group with higher likelihood of having undergone past IVF treatments (Lee et al 2011), and to primary care and general population groups.…”
mentioning
confidence: 99%
“…The evaluation of these specific worries about the baby and his/her health may be potentially useful inside the clinical practice for their possible prognostic value, considering the higher prevalence of postpartum depression in women who previously underwent ART procedure (Lee et al 2011). In particular, these negative thoughts are distinct from the usual thoughts and symptoms present in the postpartum blues (Gjerdingen et al 2008), thus requiring particular attention.…”
Section: Discussionmentioning
confidence: 99%